Sensory Arts-Based Storytelling as Critical Reflection: Tales From an Online Graduate Social Work Classroom (LEARNing Landscapes, 2021)
Drawing upon Heron and Reason’s (1997) participatory inquiry paradigm and extended epistemology, this article explores how six Master of Social Work (MSW) students engaged in sensory arts-based critical reflection concerning their social location, identities, social justice, and social policy. We share our process for creating sensory arts-based stories, the stories themselves, and pedagogical reflections. We elucidate how sensory arts-based storytelling allows learners to draw upon their strengths, unique perspectives, and experiences in the world, generating transformative understandings of social justice. Sensory arts-based storytelling holds potential as an interdisciplinary mode of critical reflection, generating inclusive learning environments oriented towards social change.
Keywords: sensory; arts-based methods; social work; critical reflection; storytelling